Морфо-функциональный анализ грудной конечности динотерия из с. Гусятин Тернопольской области - Данилова, Е.И.; Свистун, В.И. (Вестник зоологии, 1969)
The article deals with the analysis of pectoral extremity of Dinotherium levius, the bone remains of which were found in vil. Gusyatin of Ternopol region in greenish-grey sand of the Late Torton century at the depth of 11 m.
The morphologically detailed comparative description is made of the skeleton of the left pectoral extremity in D. levius. It permits some conclusions to be drawn on functional peculiarities and movements of the animal forelegs and on the basis of it the supposition on its ecology is made.